The Meaning and Contribution of Marriage Preparation Courses to the Happiness of Married Couples at Stasi Santo Paulus Beganding - Ginting, Dea Opelia Br; Bere, Paulus Halek (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Marriage preparation courses have become increasingly important for couples who wish to build a strong foundation for their relationships. These courses provide couples with the tools to understand and navigate their roles and responsibilities in a marriage. For Catholic couples, attending marriage preparation courses is seen as an essential step in preparing for a lifelong commitment, in accordance with the teachings of the Catholic Church. According to John Paul II (1981) in Familiaris Consortio, a document that outlines the duties and responsibilities of families, the preparation for marriage should be holistic, addressing not only the emotional and social aspects but also the spiritual and theological dimensions of family life. This study specifically aims to explore the meaning and impact of marriage preparation courses on the happiness of Catholic families at the St. Paul Beganding station. Using a qualitative approach, the research employed a combination of observation, interviews, and documentation techniques to gather data. The study involved 12 informants, including five married couples who had attended marriage preparation courses, one Porhanger (a community leader), and one parish priest under the St. Peter and Paul Kabanjahe parish. The findings reveal that marriage preparation courses had a significant and positive effect on the happiness of Catholic families, particularly those at the St. Paul Beganding station. The course content provided couples with a deeper understanding of their roles and duties as spouses and parents, allowing them to build stronger, more resilient relationships. Participants expressed that the courses helped them address challenges more effectively and fostered a greater sense of commitment and mutual respect. This, in turn, contributed to the overall happiness of their families. Couples who had attended the course reported stronger emotional and spiritual connections, further emphasizing the importance of comprehensive marriage preparation for long-term marital success.